The Wheat Wall-Associated Receptor-Like Kinase TaWAK-6D Mediates Broad Resistance to Two Fungal Pathogens Fusarium pseudograminearum and Rhizoctonia cerealis - Qi, Haijun; Guo, Feilong; Lv, Liangjie; Zhu, Xiuliang; Zhang, Li; Yu, Jinfeng; Wei, Xuening; Zhang, Zengyan (Frontiers in Plant Science, 2021)
The soil-borne fungi Fusarium pseudograminearum and Rhizoctonia cerealis are the major pathogens for the economically important diseases Fusarium crown rot (FCR) and sharp eyespot of common wheat (Triticum aestivum), respectively. However, there has been no report on the broad resistance of wheat genes against both F. pseudograminearum and R. cerealis. In the current study, we identified TaWAK-6D, a wall-associated kinase (WAK) which is an encoding gene located on chromosome 6D, and demonstrated its broad resistance role in the wheat responses to both F. pseudograminearum and R. cerealis infection. TaWAK-6D transcript induction by F. pseudograminearum and R. cerealis was related to the resistance degree of wheat and the gene expression was significantly induced by exogenous pectin treatment. Silencing of TaWAK-6D compromised wheat resistance to F. pseudograminearum and R. cerealis, and repressed the expression of a serial of wheat defense-related genes. Ectopic expression of TaWAK-6D in Nicotiana benthamiana positively modulated the expression of several defense-related genes. TaWAK-6D protein was determined to localize to the plasma membrane in wheat and N. benthamiana. Collectively, the TaWAK-6D at the plasma membrane mediated the broad resistance responses to both F. pseudograminearum and R. cerealis in wheat at the seedling stage. This study, therefore, concludes that TaWAK-6D is a promising gene for improving wheat broad resistance to FCR and sharp eyespot.